Gamify: how gamification motivates people to do extraordinary things - Burke, Brian
Organizations are facing an engagement crisis. Regardless if they are customers, employees, patients, students, citizens, stakeholders, organizations struggle to meaningfully engage their key constituent groups who have a precious and limited resource: their time. Not surprisingly, these stakeholders have developed deflector shields to protect themselves. Only a privileged few organizations are allowed to penetrate the shield, and even less will meaningfully engage. To penetrate the shield, and engage the audience, organizations need an edge. Gamification has emerged as a way to gain that edge and organizations are beginning to see it as a key tool in their digital engagement strategy. While gamification has tremendous potential to break through, most companies will get it wrong. Gartner predicts that by 2014, 80% of current gamified applications will fail to meet business objectives primarily due to poor design. As a trend, gamification is at the peak of the hype cycle; it has been oversold and it is broadly misunderstood. We are heading for the inevitable fall. Too many organizations have been led to believe that gamification is a magic elixir for indoctrinating the masses and manipulating them to do their bidding. These organizations are mistaking people for puppets, and these transparently cynical efforts are doomed to fail